Concessões de Florestas Públicas: realidades e discursos - Tuji, Juliana Correa (2011)
The model of concession forest in Brazil, established by Law n.11.284/06, was adopted in order to contain the increase of deforestation, tax evasion and illegal confiscation of land, mainly in the Amazon. This law definitely inserts Brazil in the world market of wood, mainly dominated by Asian countries, particularly Thailand and Indonesia. Furthermore, to the Environmental Law, this current law represents an important point in the Brazilian legal system since it inserts in the management of forest resources the private enterprise, which previously was not expressly provided for nor was there regulation. The model in question has been used by several countries, mostly Asians, however there is no news that has been successful as a sustainable activity, which does not adversely affect the Brazilian government to adopt the same system. The edition of the law was also strongly influenced by the international timber market mainly by decreasing the supply of the product as a result of the reduction of the production of Asian logging companies, from when the timber industry began to seek for new markets in search of raw material located in a strategic point to reach the markets U.S. and European regulatory and less rigorous oversight. However, for a better understanding of the issue is not enough examination of the conjecture of the world market, it is necessary also to have an understanding of the environmental crisis that the world is going through, in order to outline the situation that originated the concept of sustainable development and how it was appropriated by several discourses to legitimize the expansion of the market. With these bases, it may be possible to structure the context which created the concessions and how countries have homogenized their legislation and discourses around the protection of nature to better accommodate the financial enterprises.